Observation of Laser-Induced Bubbles in Glycerol–Water Mixtures - Laurel ONeill; Tim Kane (Fluids)
This work presents a method of directly imaging the growth and collapse of laser induced-bubbles in glycerol and water mixtures. The direct optical imaging is augmented with interferometric measurements of the vibration spectrum of the bubble-vessel system. Experimentation confirms the expectation that fluid viscosity affects the bubble formation and lifetime. During the experiment, deviation from the Rayleigh–Plesset equation is observed. Given this deviation of the observed bubble dynamics from the expected results, it is possible that the limited size of the sample volume and the walls of the container impact the bubble dynamics. The optical observations are supported by the observations of the system’s vibration spectrum.